A Comparative Study of Cholesterol Levels in Non-Pregnant Females Taking Ketogenic Versus Low Calorie Diet - Misbah Syed, Rubina Iqbal, Fatima Zahid, Samreen Manzoor, Shahzaib Wazir Qureshi, Shoaib Muhammed Daniyal (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Over the past few years, the population of Pakistan has become much aware of the need of weight loss and healthy lifestyle. We evaluated the cholesterol profiles to observe how keto diet and low-calorie diet influence the basic lipid profile of females. Aims: The aim of this study was to compare the cholesterol and triglyceride levels in adult non pregnant females taking ketogenic versus low calorie diet for a one month Methodology: The design of this study was a cross sectional study design. This study was conducted in lady reading hospital Peshawar and the duration of this study was from January 2022 to February 2022. 60 non pregnant females of age between 35-45 years with BMI ranging between 30-34.9 were included in the study. 30 were on low calorie diet, 30 were on keto diet. The serum cholesterol and triglyceride levels were calculated on day 1 and day 30 of the study. Results: The serum chloesterol levels were significantly reduced in individuals taking low calorie diet as compared to keto diet over a period of thirty days. After few weeks, anthropometric and body composition measurements revealed a significant reduction significant decrease in glucose and insulin blood levels were observed, together with a significant improvement of body weight. There was a significant, slightly decrease of LBM. A significant decrease of triglycerides, total cholesterol and LDL were observed along with a rise in HDL levels. The LH/FSH ratio, LH total and free testosterone, and DHEAS blood levels were also significantly reduced. Estradiol, progesterone and SHBG increased. The Ferriman Gallwey Score was slightly, although not significantly, reduced. Practical Implication: to determine the effects of a ketogenic diet (KD) in women age with a diagnosis of PCOS. We hypothesized that a modified KD (KEMEPHY diet) would lead to an improvement in body weight, plasma cholesterol, triglycerides, hyperinsulinemia, and hormonal outcomes Conclusion: Low calorie diet was significantly better than ketogenic diet in reducing serum cholesterol and triglyceride levels in individuals on a 30-day diet plan of respective type. Our results suggest that a ketogenic diet may be considered as a valuable nonpharmacological treatment for Polycystic ovary syndrome. Longer treatment periods should be tested to verify the effect of a ketogenic diet on the dermatological aspects of Polycystic ovary syndrome. Keywords: Cholesterol, Ketogenic Diet, Serum, Lifestyle, Low Calorie, Nutritionist